(untitled) (Research, Society and Development, 2020)
This study aims to reflect on the role of nurses in the production of knowledge in nursing from an ecosystem perspective. It is a theoretical-reflective study based on critical literature on the role of nurses in the interface of scientific knowledge from an ecosystem perspective. The results were based on two thematic axes: Knowledge production in nursing in the ecosystem context; the role of nurses in the interface between scientific knowledge, health, environment and care. It is concluded that knowledge, health, environment and user, are constantly interconnected in the nurse’s ecosystem, being the nurse responsible for building new knowledge paradigms that can cause profound changes in order to expand, organize and positively impact knowledge and do assistance.